ANTI-BACTERIAL ACTIVITY OF CHITOSAN NANOPARTICLES GEL FROM CRAB SHELL WASTE (PORTUNUS PELAGICUS) AGAINST STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI BACTERIA - L. Y., YUSAN; H., SUBAGIO (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to develop a chitosan nanoparticle gel from crab shell waste (Portunus pelagicus) by testing the anti-bacterial activity against Staphylococcus aureus and Escherichia coli. Methods: Chitosan nanoparticles gel formulation was made using spontaneous method. The gel formulation used 1% concentration of chitosan nanoparticles. Optimization of gel base and formula, including organoleptic test, homogeneity, pH determination, adhesion, spreadability and viscosity test were evaluated. Anti-bacterial activity was determined against Staphylococcus aureus and Escherichia coli bacteria. Results: The results showed that the formulation produced a stable gel with semisolid characteristics without any coarse grains, clear white and homogeneous. The pH of the formula was 5.94-6.46 and included the type of Oil in Water (O/W) gel. The formula showed adhesion of 1.05-1.97 seconds, spreadability of 5.33-5.00 cm and viscosity ranging from 7444-7792 cp. Chitosan nanoparticles gel showed the highest anti-bacterial activity with the zone of inhibition on Staphylococcus aureus of 15.37±1.34 mm and Escherichia coli of 18.33±0.25 mm with 250 mg chitosan nanoparticles gel. Conclusion: Portunus pelagicus shell waste chitosan nanoparticles produced a stable gel and showed moderate anti-bacterial activity with the highest inhibition zone at 250 mg.